ANALYSIS OF THE DIFFERENCE BETWEEN PERMANENT EMPLOYEES AND CONTRACTUAL EMPLOYEES’ WELFARE POLICIES AT PT SALIM IVOMAS PRATAMA TBK BITUNG, NORTH SULAWESI - Waloni, Verren Henny; Lapian, S. L. H. V. Joyce; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to analyze the differences in welfare policies between permanent employees and contract employees at PT Salim Ivomas Pratama Tbk, Bitung, North Sulawesi. Employee welfare is an important factor that affects job satisfaction, productivity, and loyalty to the company. However, there are often significant differences in the welfare policies provided to permanent and contract employees, which can affect their motivation and performance. The population in this study were permanent employees and non-permanent employees at PT Salim Ivomas Pratama Tbk, Bitung, North Sulawesi, totaling 136 people, namely 104 permanent employees and 32 non-permanent employees. This type of research uses comparative research which aims to see differences in the variables to be tested using Independent Sample T-Test analysis. The results of this study indicate that there is no significant difference in the welfare policies of Permanent Employees and Non-Permanent Employees at PT Salim Ivomas Pratama Tbk, Bitung, North Sulawesi.   Keywords: Employee Welfare, Company Policy, Permanent Employees, Contractual Employees